RE-READING SAIFUDDIN AMSIR’S QUR’ANIC SCHOLARS IN BETAWI - Nur Hamidah (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2023)
This article aims to examine how the role of Saifudin Amsir, who is usually known as a scholar of jurisprudence and philosophy, also contributed to the development of Qur'ān science in Betawi. This article uses descriptive-analytical research with a historical analysis approach to find out the development of tafsir books in Indonesia so that the figure of Betawi scholar Saifudin Amsir was born with his work. This article also uses a qualitative combination approach. This article proves that there is a role of Saifudin Amsir in the development of Qur'anic science in Betawi with his monumental works on the Quran, namely the book of Tafsīr Jawāhir Al-Qur`ān and the book of Al-Qur'ān Ijāzan wa Khawāṣan wa Falsafatan by Saifudin Amsir.